Organocatalytic enantioselective direct vinylogous michael addition of alpha,beta-unsaturated gamma-butyrolactam to beta-acyl acrylates and 1,2-diacylethylenes - Chen, Yi-Ru; Das, Utpal; Liu, Meng-Hsien; Lin, Wenwei (Journal of Organic Chemistry, 2015)
A highly efficient Michael addition of alpha,beta-unsaturated gamma-butyrolactam to various beta-acyl acrylates and ene-diones to provide synthetically useful compounds was developed. The products were obtained with high diastereo- and enantioselectivities (up to >25:1 dr and 99% ee) containing adjacent tertiary stereocenters.